Carbon budget in integrated aquaculture systems with Nile tilapia (Oreochromis niloticus) and Amazon river prawn (Macrobrachium amazonicum) - David, Fernanda S. [UNESP]; Proença, Danilo C. [UNESP]; Flickinger, Dallas L. [UNESP]; Wolff Bueno, Guilherme [UNESP]; Valenti, Wagner C. [UNESP] (Hindawi, 2021)
This study was centred on the carbon budget of Integrated multitrophic aquaculture (IMTA) systems in earthen ponds stocked with the freshwater Amazon river prawn (Macrobrachium amazonicum) and Nile tilapia (Oreochromis niloticus), with or without different added substrates. The experimental design was completely randomized, with three treatments and four replicates. Carbon entered the system mainly through the diet (~58–63%), inlet water (~29–34%) and absorbed gases (~5–7%). Most of it was accumulated in the sediments (~42–70%) or discharged in the outlet water (~12–13%). The tilapias converted ~12% of the carbon available into harvested biomass, and the prawns converted only ~1%. The retention of carbon inside the ponds from the inlet water was ~1 tonne ha−1, and the atmosphere ~0.1–0.3 tonnes ha−1. The carbon accumulated in the sediment was about 3.5 tonnes ha-1. Data suggest that the integrated aquaculture in stagnant earthen ponds sequesters high quantities of carbon from the nutrient-rich source water and atmosphere, and the addition of substrates at 50% of pond area do not improve the assimilation of carbon by the farmed species, having a low effect on the carbon budget.
Keywords: carbon budget; carbon sequestration; integrated system; periphyton; substrate